KESESUAIAN PENERAPAN STANDAR PELAYANAN KEFARMASIAN DI APOTEK MILIK BUMN WILAYAH KOTA MANADO - Badu, Nindi S.; Lolo, Widya A.; Jayanto, Imam (UNIVERSITAS SAM RATULANGI, 2019)
ABSTRACTThe application of pharmaceutical service standards in pharmacies in general is not in accordance with the Decree of the Minister of Health of the Republic of Indonesia at Year of 2016 concerning the Pharmaceutical Service Standards at the Pharmacy, which stipulates that all pharmaceutical personnel in carrying out their professional duties at pharmacies refer to these standards. This study aims to determine the suitability of the management of pharmacies owned by state-owned companies in the City of Manado with pharmaceutical service standards at the Pharmacy according to the Decree of the Minister of Health No. 73 of 2016. This type of research is a descriptive study. Data was collected by conducting direct observations accompanied by filling in questionnaires at 5 state-owned pharmacies in the Manado City Region. Based on the results of this study it is known that all pharmacies have met the standards of aspects of supply management, resources and the availability of facilities and infrastructure that are included in the good category. While the aspect of prescription services included in the good category as many as 2 pharmacies, with an average value for prescription services for 2 pharmacies is 72.72%. Keywoard : Pharmacy, Pharmacist, Pharmaceutical Service Standards. ABSTRAKPenerapan standar pelayanan kefarmasian di apotek pada umumnya belum sesuai dengan Peratuuran Menteri Kesehatan Republik Indonesia Tahun 2016 tentang Standar Pelayanan Kefarmasian di Apotek, yang menetapkan bahwa semua tenaga kefarmasian dalam melaksanakan tugas profesinya di apotek agar mengacu pada standar tersebut. Penelitian ini bertujuan untuk mengetahui Kesesuaian Pengelolaan Apotek milik BUMN Wilayah Kota Manado dengan Standar Pelayanan Kefarmasian di Apotek menurut Peraturan Menteri Kesehatan Republik Indonesia No. 73 Tahun 2016. Jenis penelitian ini merupakan penelitian deskriptif. Data dikumpulkan dengan cara melakukan observasi langsung disertai dengan pengisian kuesioner pada 5 apotek BUMN di Wilayah Kota Manado. Berdasarkan hasil penelitian ini diketahui bahwa seluruh apotek telah memenuhi standar dari aspek pengelolaan perbekalan, sumber daya dan ketersediaan fasilitas sarana dan prasarana yang termasuk dalam kategori baik. Sedangkan dari aspek pelayanan resep yang termasuk dalam kategori baik sebanyak 2 apotek, dengan nilai rata-rata untuk pelayanan resep 2 apotek adalah 72,72%. Kata Kunci : Apotek, Apoteker, Standar Pelayanan Kefarmasian.